2022
DOI: 10.1039/d2cc05053f
|View full text |Cite
|
Sign up to set email alerts
|

NMR methods for the analysis of mixtures

Abstract: NMR spectroscopy is a powerful approach for the analysis of mixtures. This feature article describes a selection of methods that aim to address the complexity, the low concentrations, and the changing nature that mixtures can display.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 207 publications
0
21
0
Order By: Relevance
“…40 The ability of NMR to quantify multiple species in a single experiment is particularly interesting for such analysis, but the multicomponent nature of such drugs makes 1 H NMR poorly suited to resolve and integrate signals from the individual components of complex polymers. Chemometric techniques based on 1 H NMR profiling can be used to tackle such complexity, and several papers demonstrated the utility of such methods to detect contaminated heparin samples. 41 It was recently shown that such chemometric methods can also be applied to diffusion-ordered spectroscopy (DOSY) datasets, allowing to predict the molecular weight of heparin samples.…”
Section: Nmr Methodological Developmentsmentioning
confidence: 99%
See 4 more Smart Citations
“…40 The ability of NMR to quantify multiple species in a single experiment is particularly interesting for such analysis, but the multicomponent nature of such drugs makes 1 H NMR poorly suited to resolve and integrate signals from the individual components of complex polymers. Chemometric techniques based on 1 H NMR profiling can be used to tackle such complexity, and several papers demonstrated the utility of such methods to detect contaminated heparin samples. 41 It was recently shown that such chemometric methods can also be applied to diffusion-ordered spectroscopy (DOSY) datasets, allowing to predict the molecular weight of heparin samples.…”
Section: Nmr Methodological Developmentsmentioning
confidence: 99%
“…Fig. 1A shows how 1 H NMR provides an opportunity to identify and quantify an impurity (kaempferol) present in a sample of quercetin (a flavonoid used as a food supplement). 30 While the mixture contains only two compounds, it can already be considered as ''complex'' because the two molecules have very similar structures.…”
Section: Complex Problems In a Constrained Environmentmentioning
confidence: 99%
See 3 more Smart Citations